Second Opinions: Why Canadian Doctors Do Not Always Defend Medical Dominance - Diepeveen, Benjamin (Université d'Ottawa / University of Ottawa, 2019)
Organized medicine is a uniquely powerful political force in Canada, with physician colleges and associations exerting extensive influence over healthcare provision. Their influence has contributed to what social scientists describe as medical dominance, or the exceptional power of the medical profession within the healthcare system and wider society. However, Canadian medical organizations do not consistently defend this dominance; rather, they have occasionally lent support to policy changes that, on their face, would appear incompatible with traditional conceptions of medical power and authority. Typically, these instances are explained as a simple matter of strategic retreat: medicine conceding defeat on a particular issue in an effort to save face or conserve resources, without any change in underlying beliefs. This dissertation questions that assumption, asking if at times organized medicine’s support for threats to medical dominance is instead a function of more fundamental shifts in core policy beliefs. Through a series of interviews exploring how organized medicine responded to the re-emergence of midwifery and expansions of pharmacy scope in four provinces (Alberta, Ontario, Quebec and Nova Scotia), the analysis determines that, while medicine only supported expanded pharmacy scope out of strategic retreat, there are signs of more substantive shifts in belief with respect to midwifery. This suggests that the relationship between organized medicine and traditional medical dominance is more flexible and dynamic than has been assumed.
Keywords: Medical dominance; Physicians; Pharmacy; Midwifery; Learning; Health policy